2011
DOI: 10.1007/s11368-011-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk due to consumption of vegetables contaminated with carcinogenic polycyclic aromatic hydrocarbons

Abstract: Purpose Polycyclic aromatic hydrocarbons (PAH) are persistent, toxic, and carcinogenic contaminants present in soil ecosystem globally. These pollutants are gradually accumulating in wastewater-irrigated soils and lead to the contamination of vegetables. Food chain contamination with PAH is considered as one of the major pathways for human exposure. This study was aimed to investigate the concentrations of PAH in soils and vegetables collected from wastewater-irrigated fields from metropolitan areas of Beijing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…A conversion factor of 0.085 was used to convert fresh green vegetable weight to dry weight, as described by Rattan et al (2005). Average daily vegetable intake for adults and children were considered of 0.345 and 0.232 kg person −1 d −1 , respectively, while the average adult and children body weights were considered of 63.9 and 32.7 kg, respectively, as used in the previous studies (Ge, 1992;Wang et al, 2005;Khan and Cao, 2012).…”
Section: Daily Intake Of Pahsmentioning
confidence: 99%
“…A conversion factor of 0.085 was used to convert fresh green vegetable weight to dry weight, as described by Rattan et al (2005). Average daily vegetable intake for adults and children were considered of 0.345 and 0.232 kg person −1 d −1 , respectively, while the average adult and children body weights were considered of 63.9 and 32.7 kg, respectively, as used in the previous studies (Ge, 1992;Wang et al, 2005;Khan and Cao, 2012).…”
Section: Daily Intake Of Pahsmentioning
confidence: 99%
“…Numerous studies have demonstrated that vegetables can take up and accumulate PAHs from the contaminated environment (Wennrich et al, 2002;Zohair et al, 2006;Khan and Cao, 2012). The mechanisms responsible for the PAH transfer to plant tissues primarily include sorption from soil particles, uptake by the roots through transpiration, and absorption through the waxy leaf cuticle or through stomata (Wild et al, 2004;Meudec et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heavy pollution at an e-waste recycling area may result in an elevated uptake of PAHs into vegetables. Because diet is considered the major source of human exposure to PAHs (Phillips, 1999) and vegetables are the basic food in the Chinese diet, potential health risks might be involved in consuming these contaminated vegetables (Tao et al, 2004;Zhao et al, 2009;Khan and Cao, 2012). However, most previous studies have focused on contamination by PCBs and BFRs (Ma et al, 2009a;Zhao et al, 2009;Wang et al, 2011a), and few studies were performed on the accumulation, distribution, and potential health risk of PAHs, especially in vegetables grown near e-waste recycling areas.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that human exposure to PAHs occurs more prominently via soils than via air or water (Torre-Roche et al, 2009). PAHs in soils, once accumulated, lead to contamination of vegetables and other crops to enter the food chain as one of the key human exposure routes (Yap et al, 2010;Khan and Cao, 2011).…”
Section: Introductionmentioning
confidence: 99%